Single-stranded DNA phages: from early molecular biology tools to recent revolutions in environmental microbiology - Székely, Anna J.; Breitbart, Mya (FEMS microbiology letters, 2016)
Single-stranded DNA (ssDNA) phages are profoundly different from tailed phages in many aspects including the nature and size of their genome, virion size and morphology, mutation rate, involvement in horizontal gene transfer, infection dynamics and cell lysis mechanisms. Despite the importance of ssDNA phages as molecular biology tools and model systems, the environmental distribution and ecological roles of these phages have been largely unexplored. Viral metagenomics and other culture-independent viral diversity studies have recently challenged the perspective of tailed, double-stranded DNA (dsDNA) phages, dominance by demonstrating the prevalence of ssDNA phages in diverse habitats. However, the differences between ssDNA and dsDNA phages also substantially limit the efficacy of simultaneously assessing the abundance and diversity of these two phage groups. Here we provide an overview of the major differences between ssDNA and tailed dsDNA phages that may influence their effects on bacterial communities. Furthermore, through the analysis of 181 published metaviromes we demonstrate the environmental distribution of ssDNA phages and present an analysis of the methodological biases that distort their study through metagenomics. In light of the recent recognition of the high diversity and cosmopolitan distribution of single-stranded DNA phages, this manuscript presents an overview of the major differences between single-stranded and double-stranded DNA phages that may influence their effects on bacterial communities and make their simultaneous study in environmental samples challenging.